2018
DOI: 10.1016/j.dsr2.2017.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple gas reservoirs are responsible for the gas emissions along the Marmara fault network

Abstract: On continental margins, upward migration of fluids from various sources and various subsurface accumulations, through the sedimentary column to the seafloor, leads to the development of cold seeps where chemical compounds are discharged into the water column. MarsiteCruise was undertaken in November 2014 to investigate the dynamics of cold seeps characterized by vigorous gas emissions in the Sea of Marmara (SoM). Please note that this is an author-produced PDF of an article accepted for publication following p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 86 publications
1
45
0
Order By: Relevance
“…However, there is no systematic relationship between gas composition and proximity to fault zones. For instance, thermogenic methane dominates fluid emissions over the top of the Central High and within the MMF deformation zone in the Western High (Bourry et al, 2008;Çağatay et al, 2017;Ruffine et al, 2017) but we showed that the distributions of seepages have different characteristics at both locations (broad leakage zone over an anticline vs. 2 km wide swath along the main fault). Close examination of the relationship between faults and gas emissions within seafloor deformation zones also shows that even at the 10-100 m scale of AUV maps and submersible observations (Figure 7 and Grall et al, this issue), many acoustic anomalies are not located on the outcrops of small faults.…”
Section: Gas Migration Pathways In Shallow Sedimentsmentioning
confidence: 52%
See 2 more Smart Citations
“…However, there is no systematic relationship between gas composition and proximity to fault zones. For instance, thermogenic methane dominates fluid emissions over the top of the Central High and within the MMF deformation zone in the Western High (Bourry et al, 2008;Çağatay et al, 2017;Ruffine et al, 2017) but we showed that the distributions of seepages have different characteristics at both locations (broad leakage zone over an anticline vs. 2 km wide swath along the main fault). Close examination of the relationship between faults and gas emissions within seafloor deformation zones also shows that even at the 10-100 m scale of AUV maps and submersible observations (Figure 7 and Grall et al, this issue), many acoustic anomalies are not located on the outcrops of small faults.…”
Section: Gas Migration Pathways In Shallow Sedimentsmentioning
confidence: 52%
“…Consequently, the presence of gas emissions within a deformation zone is not a demonstration that fluids migrate along the deeper part of the fault zone. Geochemical evidence may be considered more demonstrative and it shows that the expulsion of deep originated fluids tends to be focused at specific locations (fault intersections, anticline top, mud diapir or conduit) (Burnard et al, 2012;Ruffine et al, 2017;Tryon et al, 2010). However, there is no systematic relationship between gas composition and proximity to fault zones.…”
Section: Gas Migration Pathways In Shallow Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a strategy allowed us to detect and sample 18 gas seeps. It has been shown that the gas bubbles emitted at the seafloor are mixtures of primary and secondary microbial gases with thermogenic and mantlederived gases with very asymmetric contribution of each source (Ruffine et al, 2018a). The sediments in the vicinity of the seeps host living benthic Foraminifera, and a study from samples collected on the Central High and the Çınarcık Basin show that Bolivina vadescens and Globobulimina affinis are the two dominant species at the study areas (Fontanier et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Basin (Armijo et al, 2005). Later on, detailed seafloor observations and sampling of gas, pore waters, sediments, gas hydrates and carbonate crusts were made during Marnaut and Marsite cruises using Nautile manned submersible and ROV Victor 6000 dives in 2007 and 2014 (Henry et al, 2007;Ruffine et al, 2015).…”
Section: Introductionmentioning
confidence: 99%